Karakterisasi Biosorben Magnetik Ampas Kopi untuk Penyisihan Ion Timbal (Pb) - Irza, Tsaqif Aufa; Khadafi, Muammar; Suhendrayatna, Suhendrayatna; Syaubari, Syaubari (Politeknik Negeri Lhokseumawe, 2024)
Industrial waste often contains heavy metals which are dangerous for human health and the environment, so effective and environmentally friendly waste processing is very necessary. This research aims to optimize the use of synthetic magnetic bioadsorbent from coffee grounds to remove the heavy metal lead (Pb) from industrial waste. Magnetic bioadsorbent was synthesized from coffee grounds by carbonizing the coffee grounds at a temperature of 600℃ for 3 hours and activated using 100 mL of 1 M HCl. The adsorption time and adsorbate concentration were tested at values of 30, 60, and 90, as well as 0.661, 1.494, 2.29, and 3 (mg/L) adsorbate, and adsorption temperatures of 30 ℃, 40 ℃, and 50 ℃. Meanwhile, carbonization temperature, coffee grounds weight, and activator concentration were used as fixed variables. In this research, the independent variables are adsorption time, adsorbate concentration, and adsorption temperature. while the fixed variables are carbonization temperature, coffee grounds weight, and activator concentration. The results of this research show that it was successful in linking the magnetite compound to the adsorbent and it can be seen from the results of FTIR analysis that there are FeO groups at a wave of 560 cm-1 and in the XRD characterization test, Fe groups are found at a wave of 35o, and based on the characterization using SEM there is a change in area surface before and after synthesis due to the presence of magnetite particles that stick to the surface, causing the pores to become smaller.